Analysis and evaluation of factors affecting the motivation of construction workers - Thuy, Nguyen Thi; Toan, Nguyen Quoc; Hanh, Nguyen Thi My; Tuan, Le Van (Edelweiss Applied Science and Technology, 2024)
The characteristics of the construction works are the participation of many fields and many jobs with different requirements. Therefore, in construction projects, even when applying science, technology and automation, the construction workers also play an important role. The construction workers are the main force and directly perform the tasks of creating construction products. For desiring to improve the labor productivity in the construction industry, research on the construction workers is focused increasingly. This paper learns about the factors which affect the motivation of the construction workers. Analytical Hierarchy Process (AHP) method is used to analyze and evaluate the affecting factors the work motivation of the construction workers. The ranking results of the factors show that the factors which are from the employer, have a strong impact on their work motivation. These factors are such as salary, bonus and welfare, labor management method, work discipline, regular job guarantee. They are factors with high weight and making decisive to the work motivation of the construction workers. Meanwhile, factors which are from employees, have less impact on their work motivation. This result is consistent with current reality.